A Study on Tax Payer Perception on Tax E-Filling in Less Developed Areas in Malaysia - Arunasalam, Kavitha (International Journal of Psychosocial Rehabilitation, 2020)
(Tax e-Filing is an e-Government service which has been implement by many countries as of today. In year 2005, Inland Revenue Board (IRB) of Malaysia has a shift in pattern by implementing e-Filing which comes under Self-Assessment System (SAS) and will focus more on audit field. E-Filing process is an easier system, accurate, fast and secure in terms of payments. The researcher for this present study aims to investigate individual taxpayer’s perception on tax E-Filling in less developed areas in Malaysia. In Malaysia, incentives and special tax cuts from Government are available for companies that sets up operations in less-developed areas. The researcher has used this incentive as a method to determine less developed areas and focus this research in Segamat, Johor and Hilir Perak. The researcher has adopted quantitative method by conducting interview among 7 individuals in Segamat and 7 individuals in Hilir Perak. The result from this study indicates that perceived ease of use and tax general knowledge on e-Filling system impacts taxpayer’s acceptance on e-Filling in less developed areas in Malaysia and taxpayers in less developed areas generally do not have issue with the perceived credibility of the system. The implication of this study suggests that Inland Revenue Board (IRB) should increase and strengthen their awareness programs in less developed areas in Malaysia to educate taxpayers so that it will simultaneously improve the attitude of taxpayers to use this electronic system.